Cross-Sectional Inflation Asymmetries and Core Inflation: A Comment on Bryan and Cecchetti - Verbrugge, Randal J. (The Review of Economics and Statistics, 1999)
This paper reexamines the evidence relating core inflation to cross-sectional inflation asymmetry using statistical measures that are robust to the criticism of Bryan and Cecchetti. The results here suggest that there does exist significant positive correlation between core inflation and cross-sectional inflation asymmetry, but only at the monthly frequency. Furthermore, a sampling problem is highlighted which underscores the importance of careful Monte Carlo analysis when exact small-sample distributions are unknown.